Analysis of Entrepreneurial Skills In Growing Competitive Advantages In "Fresh Milk" Micro, Small, And Medium Enterprises (MSMEs) In Gresik District - Sutono, Sutono (El-Qist: Journal of Islamic Economics and Business (JIEB), 2023)
This study investigates the role of entrepreneurial skills in enhancing competitive advantage among “Fresh Milk” Micro, Small, and Medium Enterprises (MSMEs) in Randu Padangan Village, Gresik, Indonesia. Employing a quantitative research design with a saturated sample of 37 entrepreneurs, the study utilized a structured questionnaire and SPSS-based statistical analysis, including t-tests and determination coefficient (R²) analysis. The results confirm that entrepreneurial skills significantly and positively influence competitive advantage, with a determination coefficient of 91.9%, indicating that nearly all competitive advantage can be attributed to the entrepreneurs’ competencies. The findings offer empirical evidence for the critical function of entrepreneurial capacity—even in low-formal-education settings—in driving rural MSME performance. This study provides a microeconomic lens on how technical, social, and managerial skills among grassroots dairy entrepreneurs contribute to resilience and differentiation in a highly competitive market. Its contribution to international discourse lies in framing entrepreneurial skill development as a vital mechanism for achieving sustainable local economic competitiveness. Future research may expand this framework to cross-country comparisons of MSME ecosystems, examine digital entrepreneurship interventions, or analyze how informal entrepreneurial learning influences sectoral innovation in emerging markets.